1997
DOI: 10.1046/j.1365-2346.1997.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

The optimal dose of local anaesthetic in the orthogonal two-needle technique. Extent of sensory block after the injection of 20, 30 and 40 mL of anaesthetic solution

Abstract: Ninety patients undergoing scheduled upper limb orthopaedic surgery were studied to determine the optimal anaesthetic dose using the 'orthogonal two-needle technique'. The patients were randomly assigned to one of three groups to receive one of three different volumes (20, 30 and 40 mL) (n = 30) of anaesthetic solution (a mixture of equal parts of 0.5% bupivacaine with adrenaline 1:200,000 and 2% lignocaine). A significant correlation was found between the volume injected and the anaesthetic spread for all tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…8 In this study, they concluded that success rate of blockade was higher in groups where 30 and 40 mL local anesthetic was administered.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…8 In this study, they concluded that success rate of blockade was higher in groups where 30 and 40 mL local anesthetic was administered.…”
Section: Discussionmentioning
confidence: 81%
“…In the current study, we used 30 mL and 60 mL local anesthetics in different concentrations. [8][9][10][11] Risk of systemic toxicity especially rises in case of advanced age, poor health, liver and kidney failure and pregnancy. Therefore, volume is kept as low as possible in the studies with the aim of achieving a successful blockade.…”
Section: 10mentioning
confidence: 99%
“…In studies where local anesthetic agents more than 30 ml were used, better drug distribution in the axillary region with higher success rates have been demonstrated [22, 23]. Besides, as reported in the literature, local anesthetic agent applied lateral to the median nerve spreads along the axillary artery and easily blocks the musculocutaneous nerve [11, 13, 24].…”
Section: Discussionmentioning
confidence: 99%